Description of the nymph of Anacroneuria singularis Righi-Cavallaro & Lecci (Plecoptera: Perlidae) and a new locality record for northern Brazil - Ribeiro, José Moacir Ferreira; Gorayeb, Inocêncio De Sousa; Bispo, Pitágoras Da Conceição (Zootaxa, 2015)
The last instar nymph of Anacroneuria singularis Righi-Cavallaro & Lecci is described and figured from reared specimens collected in Pará State, Brazil, a new locality record for Brazil. The nymphs of this species differ from other known species by the uniformly dark brown anterior of the head and the ochraceous spots of the pronotum.